STATE SYSTEM OF LEGAL INFORMATION AND MAIN DIRECTIONS OF ITS DEVELOPMENT - A. V. Bobtsov (Informatika)
The questions of development, establishment and operation of the state System of Legal Information of the Republic of Belarus, its main elements and key directions of the development and improvement are considered.